The distribution of the Dadanitic inscriptions according to their content and palaeographical features - Hidalgo-Chacón Díez, María del Carmen (Proceedings of the Seminar for Arabian Studies, 2015)
The Dadanitic inscriptions are found in the oasis of al-ʿUlā and Madāʿin Sāliḥ (north-west Saudi Arabia). They have been incised or carved in the rock-face as well as on stones (stelae). The inscriptions can be classified by their content as follows: votive inscriptions, which are dedicated to a god, the majority to the Dadanititc chief deity Ḏġbt; funerary inscriptions, most of which have been recorded close to the tombs in Jabal al-Khuraybah; royal inscriptions, which make reference to the place name Ddn (modern alʿUlā), mlk ddn, or to the group name Lḥyn, mlk Iḥyn; and finally the dated inscriptions, which present a series of royal and governor years. In spite of this it is impossible to offer a chronology of the inscriptions. Regarding the palaeography, we can find inscriptions recorded in a formal or an informal script, inscriptions which contain a mixture of letter-forms, and carved inscriptions in which the last lines are incised. The content of the inscriptions and to some extent their palaeography differs considerably from place to place, especially in al-ʿUlā. The purpose of this paper is to present the geographical distribution of known inscriptions within these two oases with regard to their philological and cultural content and palaeography.